2019
DOI: 10.1016/j.intimp.2019.105951
|View full text |Cite
|
Sign up to set email alerts
|

The tiliroside derivative, 3-O-[(E)-(2-oxo-4-(p-tolyl) but–3–en–1–yl] kaempferol produced inhibition of neuroinflammation and activation of AMPK and Nrf2/HO-1 pathways in BV-2 microglia

Abstract: Neuroinflammation is now widely accepted as an important pathophysiological mechanism in neurodegenerative disorders, thus providing a critical target for novel compounds. In this study, 3-O-[(E)-(2-oxo-4-(p-tolyl) but 3 en 1 yl] kaempferol (OTBK) prevented the production of pro-inflammatory mediators TNFα, IL-6, PGE2 and nitrite from BV-2 microglia activated with LPS and IFN. These effects were accompanied by a reduction in the levels of pro-inflammatory proteins COX-2 and iNOS. Involvement of NF-B in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Neuroinflammation can arise from an imbalance between proinflammatory and anti-inflammatory phenotypes favoring the former, with a reversal in the balance ameliorating disease progression, including stroke [44]. The presence of IRF5, IRF8, P2X4R, P2X7R, and P2Y12R promotes microglia polarization towards proinflammatory phenotypes, while CD163, CD206, arginase 1, Ym-1, Nrf2, Sirt1, and Heme Oxygenase-1 (HO-1) shift microglia to anti-inflammatory phenotypes [27,[45][46][47][48]. We found that cerebral ischemia-associated neuroinflammation was accompanied by the activation of microglia and astrocytes, along with the reduction of neurons and compromise of the blood-brain barrier tight junction.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation can arise from an imbalance between proinflammatory and anti-inflammatory phenotypes favoring the former, with a reversal in the balance ameliorating disease progression, including stroke [44]. The presence of IRF5, IRF8, P2X4R, P2X7R, and P2Y12R promotes microglia polarization towards proinflammatory phenotypes, while CD163, CD206, arginase 1, Ym-1, Nrf2, Sirt1, and Heme Oxygenase-1 (HO-1) shift microglia to anti-inflammatory phenotypes [27,[45][46][47][48]. We found that cerebral ischemia-associated neuroinflammation was accompanied by the activation of microglia and astrocytes, along with the reduction of neurons and compromise of the blood-brain barrier tight junction.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia, in the alternative activation polarization, release Transforming Growth Factor (TGF-β), IL-4, and IL-10, with the consequences of suppressing inflammation and restoring homeostasis. The presence of P2X4R, P2X7R, and P2Y12R promote microglia polarization towards the classical activation state, while CD163 and arginase 1 promote polarizing microglia towards the alternative activation state [32,[38][39][40][41][42]. Alterations in microglia polarization favoring the classical activation state occurred in LPS/IFN-γ-stimulated neuron/glia cultures and cerebral I/R-injured cortical brains.…”
Section: Discussionmentioning
confidence: 94%
“…As with macrophages, microglia adopt a series of molecular and biochemical events to switch genetic programs, morphological cytoskeletons, cell membrane surface presentation, and functional outcomes. The rising of pro-inflammatory and the subsiding of anti-inflammatory phenotypes of microglia have been implicated in various neurodegenerative diseases as well as a reversal in the balance of ameliorate disease progression [38][39][40][41]. Typically, neurotoxic cytokines such as TNF-α, IL-1β, IL-18, IL-6, IFN-γ, NO, PGE2, and free radicals come from classical activation polarized microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, tiliroside prevented the phosphorylation of p65 subunit of NF-kB, which is one of the critical steps in the microglia NF-kB activation pathway, after stimulation of BV-2 microglia with LPS and IFNγ. The mouse hippocampal HT22 neuron cell line in medium containing LPS + BV-2 stimulated by IFNγ resulted in reduced cell viability and generation of reactive species of oxygen, when these cells were exposed to tiliroside, indicating no damage to neural cells or generation of oxidative stress, besides having promoted the activity of the AMPK and Nrf2/HO-1 pathways responsible for suppressing neuroinflammation ( Velagapudi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%